Postmastectomy Late Breast Reconstruction with Transverse Rectus Abdominis Flap after Primary Closure with Latissimus Dorsi - Edmilson Micali; André Mattar; Ana Claudia Benjamim Burattini; Luiz Henrique Gebrim; René Aloisio da Costa Vieira (Indian Journal of Plastic Surgery)
Locally advanced breast cancer (LABC) is common in countries where organized screening is not effective. Although neoadjuvant therapy increases resectability, many patients undergo mastectomy and, in some cases, flaps are necessary for primary closure of the chest wall. Despite a worse prognosis, some of these women will achieve long-term survival and may require breast reconstruction. The literature on the subject is scarce. We present the cases of two patients with LABC undergoing neoadjuvant chemotherapy, mastectomy with extensive soft-tissue resections in the anterior chest wall, and closure with extended V-Y latissimus dorsi (LD) myocutaneous flaps. After 2 years of follow-up, they were without recurrence. They were submitted to a delayed breast reconstruction using a bipedicled transverse rectus abdominis myocutaneous (TRAM) flap. To our knowledge, this is the first publication reporting secondary reconstruction with TRAM flap after primary closure of the chest wall with LD for LABC.